Existence of Solutions of Fractional Differential Equation with p-Laplacian Operator at Resonance - Zhigang Hu; Wenbin Liu; Jiaying Liu (Abstract and Applied Analysis)
By using the extension of Mawhin’s continuation theorem due to Ge, we consider boundary value problems for fractional p-Laplacian equation. A new result on the existence of solutions for the fractional boundary value problem is obtained, which generalizes and enriches some known results to some extent from the literature.